The Contribution of Gestures to the Semantics of Non-Canonical Questions. (14th June 2021) - Ippolito, Michela
Abstract: The symbolic gesture MAT ( mano a tulipano ) used by native speakers of Italian characterizes non-canonical wh questions when used both as a co-speech and pro-speech gesture. MAT can be executed with either a fast tempo contour or a slow tempo contour. Tempo is semantically significant: descriptively, a fast tempo characterizes a biased but information-seeking non-canonical question; a slow tempo characterizes a rhetorical non-canonical question. I argue that the fast contour is the default tempo of MAT and that it brings about a biased interpretation. Slowing down the movement occurs when the feature [slow] is added: the semantic contribution of this feature is to add the presupposition that the question is resolved in the conversational context, resulting in the rhetorical interpretation of the question.